2020
DOI: 10.33899/ijvs.2019.126069.1224
|View full text |Cite
|
Sign up to set email alerts
|

Detection of lead, chromium and cobalt in meats of cattle and buffalo from retails of Mosul city

Abstract: Lead (Pb), chromium (Cr) and cobalt (Co) were investigated in 160 local and imported meat samples of cattle and buffalo collected from markets of Mosul city by using Atomic Absorption Spectrophotometer (AAS). Results reported mean concentrations of Pb and Cr in local cattle meat 0.136 and 0.0651 mg/kg, respectively significantly higher than that reported for Co 0.008 mg/kg. In imported cattle meat, results revealed that Pb presented a mean concentration 0.182 mg/kg significantly higher than that presented by C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…The clear negative comparison indicated that Hg/Cd, Cr/Cu, and Cr/Cd were likely to come from similar sources. Wastewater, municipal waste, industrial effluents, and agrochemical waste from nearby villages could provide a possible anthropogenic source of these metals (30).…”
Section: Discussionmentioning
confidence: 99%
“…The clear negative comparison indicated that Hg/Cd, Cr/Cu, and Cr/Cd were likely to come from similar sources. Wastewater, municipal waste, industrial effluents, and agrochemical waste from nearby villages could provide a possible anthropogenic source of these metals (30).…”
Section: Discussionmentioning
confidence: 99%
“…Lead toxicity is a metal poisoning triggered by the accumulation of lead in the tissues (10). It is a potent neurotoxic agent, affecting nervous system (2,3).…”
Section: Discussionmentioning
confidence: 99%
“…In Pyrex test tubes, tissues of fish organs have been dried at a stable weight of 48 hrs at 60ºC. Analysis was carried out according to the procedure described by (15). Dried tissues with concentrated sulphoric acid and perochloric acid were weighed and digested at 350 rpm.…”
Section: Methodsmentioning
confidence: 99%